Behavioral Technology Acceptance Model In Health Care Industry: Systematic Literature Review - agustini, kamelia (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Researchers found the identification of problems from the ten research gap journals discussed, namely the absence of breadth and depth with other variables that will be tested on TAM and potential applications that can contribute, there must be refinement of the proposed model, there are still areas that can be expanded and improved to improve TAM predictive performance (1). This research is a systematic literature review that discusses descriptively about the components of the Technology Acceptance model in health care and makes a conceptual framework in health care. Articles are taken from three databases, namely EBSCOhost, Proquest, Emerald with search limitations, namely academic journals, article format and in English. From 3,800 articles, 750 articles were obtained which will be screened with the appropriate title and abstract criteria. Based on the full text screening, 255 articles were obtained with the criteria of Research focus, unit of analysis, data collection unit, context, evidence based healthcare. After that, 52 final papers to be reviewed were obtained with details Emerald 6 articles, Proquest 18 articles, EBSCOhost 28 articles. After reviewing 52 journals based on full content, systematic literature review and evidence based healthcare, the synthesized journals were 12 journals TAM has widespread application in explaining the technology acceptance model in the health care industry. The increase in the use of TAM appears to be justified by the many associations defined by TAM that apply in the health care industry setting (2). Perhaps the most impressive is that the relationship between external variables such as practical experience and skills on the usability of the connected health technologies which is influenced by trust and culture that results in the use of health applications in digital media (3).